Research trends in Korean nursing students’ patient safety competency: A scoping review - Haejin Kim; Inju Hwang (The Journal of Korean Academic Society of Nursing Education, 2026)
Purpose: This scoping review mapped research on Korean nursing students’ patient-safety competency to inform future patient-safety education and subsequent study design.Methods: A literature search was conducted across domestic (RISS [Research Information Sharing Service], KISS [Korean studies Information Service System], DBpia, and ScienceON) and international (PubMed, CINAHL [Cumulative Index to Nursing and Allied Health Literature], and Web of Science) databases. Studies published in Korean or English were included if they focused on Korean nursing students and addressed patient-safety competency as an integrated concept. Data were extracted using a structured framework and then analyzed. Factors related to patient-safety competency were synthesized using constant comparative analysis.Results: Twenty studies were included in the analysis. Most studies employed quantitative designs and focused on senior nursing students with clinical practicum experience. The PSCSE (Patient Safety Competency Self-Evaluation) tool was the most frequently used measurement instrument. Factors related to patient-safety competency were clustered into four conceptual domains: cognitive competencies, interpersonal and performance-related competencies, professional identity and ethics, and personal and learning-related factors. Five intervention studies reported improvements in patient-safety knowledge and skills, while changes in attitudes varied according to academic year and instructional approach.Conclusion: Research on patient-safety competency among Korean nursing students has increased in recent years, reflecting a multidimensional understanding of competency. However, reliance on cross-sectional designs and self-reported measures limits the ability to explain how patient-safety competency develops and transfers to clinical practice. Future research should employ longitudinal and mixed-method designs and incorporate performance-based assessments across the nursing curriculum.